An Improved Tone Reservation Scheme in OFDM Systems for Adaptive Amplitude Clipping - Yang Song; Chaoshi Cai; Jianping Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Orthogonal frequency division multiplexing(OFDM) suffers from a high peak to average power ratio(PAPR).  Tone reservation (TR) technology is considered as one of the most promising methods because of no additional distortion, no side information, and low implementation cost. However, in all PAPR reduction schemes，determining the optimal target clipping level is difficult. In this paper, we consider an adaptive amplitude least squares approximation(AALAS-TR) algorithm. Adjust adaptive optimal convergence factor for initial clipping threshold. That is results an approximately PAPR reduction performance with a low computational complexity. Simulation results show that the proposed algorithm can achieve better PAPR reduction as that different clipping threshold .